A Note to Vladimir Beneševič (1874–1938) Penned by Ulrich von Wilamowitz-Moellendorﬀ (1848–1931) - Kostyleva, Tatiana (Hyperboreus, 2019)
A short undated note to Vladimir Beneševič ﬁled under 192.2.43.1r and housed in St Petersburg Branch of the Archive of the Russian Academy of Sciences is a postcard written by Ulrich von Wilamowitz-Moellendorﬀ and dispatched at some point in the course of the correspondence around what turns out to be a request for photographs of certain Sinai MSS. Further archival documents and published letters instrumental in setting the scene are cited to the result that the key to the correct understanding of the note oﬀered for publication here lies in the Zutritt to the Sinai holdings Beneševič enjoyed.